Psychometric Properties of Childhood Trauma Questionnaire - Short Form (CTQ-SF) Indonesian Version - Fitri Andriyani (Analitika: Jurnal Magister Psikologi UMA, 2022)
Abuse and neglect are increasingly occurring in various regions, including in Indonesia. The diversity of abuse and neglect in childhood and adolescence have an impact on neurobiological function damage so that it has long-term impacts on individuals who experience it. Unfortunately, in Indonesia there is no screening tool to assess the trauma of abuse and neglect in childhood and adolescence. This study aims to translate and obtain psychometric property of the Childhood Trauma Questionnaire (CTQ-SF) consisting of physical, emotional and sexual violence as well as physical and emotional neglect dimensions. The translation shows that the Indonesian version of the CTQ-SF has a good level of equivalence with the CTQ-SF. In addition, the classical test theory approach showed that the Indonesian version of CTQ-SF had a high reliability by the need of reviewing of the three items on the sexual abuse dan physical neglect dimensions. Nevertheless, a multidimensional approach of confirmatory factor analysis showed that the Indonesian version of CTQ-SF model was fit to measure the level of maltreatment (abuse and neglect) experience among adolescents in Indonesia